Non-conventional Yeast in the Wine Industry - Jose Manuel Guillamon (Frontiers Research Topics, 2017)
Saccharomyces cerevisiae strains that exhibit high ethanol tolerance and excellent fermentative ability are extensively used in winemaking as selected starters. However, a side-effect of the widespread use of these commercial starter cultures is the elimination of native microbiota, which might result in wines with similar analytical and sensory properties, depriving them from the variability, complexity and personality that define the typicality of a wine. Nonetheless, a way of balancing control and yeast population diversity during wine fermentation is the selection of non-Saccharomyces yeasts with optimal oenological traits. Therefore, a current trend in enology is the implementation of mixed- or multi-starters cultures, combining S. cerevisiae that remains the yeast species required for the completion of fermentation and non-Saccharomyces yeasts isolated from the native flora of grape juices. This research topic mainly deals with possible applications of different non-Saccharomyces yeast to wine production such as aroma production, ethanol reduction or biocontrol.Saccharomyces cerevisiae strains that exhibit high ethanol tolerance and excellent fermentative ability are extensively used in winemaking as selected starters. However, a side-effect of the widespread use of these commercial starter cultures is the elimination of native microbiota, which might result in wines with similar analytical and sensory properties, depriving them from the variability, complexity and personality that define the typicality of a wine. Nonetheless, a way of balancing control and yeast population diversity during wine fermentation is the selection of non-Saccharomyces yeasts with optimal oenological traits. Therefore, a current trend in enology is the implementation of mixed- or multi-starters cultures, combining S. cerevisiae that remains the yeast species required for the completion of fermentation and non-Saccharomyces yeasts isolated from the native flora of grape juices. This research topic mainly deals with possible applications of different non-Saccharomyces yeast to wine production such as aroma production, ethanol reduction or biocontrol.